2022
DOI: 10.3389/fmars.2022.868261
|View full text |Cite
|
Sign up to set email alerts
|

High Diazotrophic Diversity but Low N2 Fixation Activity in the Northern Benguela Upwelling System Confirming the Enigma of Nitrogen Fixation in Oxygen Minimum Zone Waters

Abstract: Oxygen minimum zones (OMZs) have been suggested as a suitable niche for the oxygen-sensitive process of biological fixation of dinitrogen (N2) gas. However, most N2 fixation rates reported from such waters are low. This low N2 fixation activity has been proposed to result from the unusual community of N2 fixers, in which cyanobacteria were typically underrepresented. The Northern Benguela Upwelling System (North BUS) is part of one of the most productive marine ecosystems and hosts a well-developed OMZ. Althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…The observed physical-biological coupling in Lake Tanganyika, a model system with respect to its hydrodynamics, may help to explain why N 2 fixation rates are generally low (<5 nM d −1 ) in some marine upwelling regions 15 , 22 , 26 28 , 30 , 80 , 81 . Many of these upwelling systems are also associated with gammaproteobacterial heterotrophic and often chemotactic diazotrophs 79 , like Pseudomonas 24 , 31 , 35 , 80 , 82 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed physical-biological coupling in Lake Tanganyika, a model system with respect to its hydrodynamics, may help to explain why N 2 fixation rates are generally low (<5 nM d −1 ) in some marine upwelling regions 15 , 22 , 26 28 , 30 , 80 , 81 . Many of these upwelling systems are also associated with gammaproteobacterial heterotrophic and often chemotactic diazotrophs 79 , like Pseudomonas 24 , 31 , 35 , 80 , 82 .…”
Section: Resultsmentioning
confidence: 99%
“…The observed physical-biological coupling in Lake Tanganyika, a model system with respect to its hydrodynamics, may help to explain why N 2 fixation rates are generally low (<5 nM d −1 ) in some marine upwelling regions 15 , 22 , 26 28 , 30 , 80 , 81 . Many of these upwelling systems are also associated with gammaproteobacterial heterotrophic and often chemotactic diazotrophs 79 , like Pseudomonas 24 , 31 , 35 , 80 , 82 . Moreover, when highly stratified conditions develop in marine upwelling regions (e.g., coastal sulfidic event 83 ), niches for phototrophic green sulfur bacteria become favorable 84 , consistent with observations in Lake Tanganyika’s Northern basin (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Under Mo-depleted conditions, the alternative nitrogenases were thought to fix N 2 . ,, However, the co-expression of all three nitrogenases occurs under conditions of various metal availability, and only a few studies provide evidence for the significant contribution of alternative nitrogenases. ,, The distribution of Mo-based metabolic processes in hot springs was not necessarily dependent on the soluble Mo concentration . The link between trace metal concentrations and nitrogenase activity is not always straightforward. , Therefore, there may be other controls on nitrogenase activity. …”
Section: Environmental Implicationsmentioning
confidence: 99%
“…Furthermore, the high nitrate (NO 3 − ) concentration often present in ODZs may not inhibit the growth of the UCYN‐A/haptophyte symbiosis, which can fix N 2 in NO 3 − ‐rich waters (Mills et al, 2020 ), an ability also observed in Crocosphaera watsonii (UCYN‐B) (Dekaezemacker & Bonnet, 2011 ; Großkopf & LaRoche, 2012 ). To date, UCYN‐B and non‐cyanobacterial diazotrophs have been found in oxygen‐deficient waters (Bonnet et al, 2013 ; Fernandez et al, 2011 ; Jayakumar et al, 2017 ; Jayakumar & Ward, 2020 ; Loescher et al, 2014 ; Löscher et al, 2020 ), whereas UCYN‐A has been detected in the Eastern Tropical North Pacific (ETNP), the Eastern Tropical South Pacific (ETSP) and the Northern Benguela Upwelling system, but only within their oxygenated waters (Reeder et al, 2022 ; Turk‐Kubo et al, 2014 , 2021 ; White et al, 2013 ). Little is known about the ecology of UCYN‐A in ODZs, therefore, providing information on its distribution in these oceanic regions is of utmost importance for a better understanding of the players involved in N fixation in ODZs.…”
Section: Introductionmentioning
confidence: 99%